Evaluation of the Power Up program: a health promotion program encouraging healthy lifestyle habits among youth in summer day camps—study protocol - Larose, David; Chih-Shing Chen, Melvin; Paracini, Tania; Panahi, Shirin; Yessis, Jennifer; Tremblay, Angelo; Drapeau, Vicky (Frontiers in Public Health, 2025)
IntroductionDuring the summer holidays, children often demonstrate reduced physical activity and poorer dietary habits, largely attributed to the lack of structured routines and supervision that school provides. Summer camps have the potential to offer youth engaging and organized activities and serve as an environment for promoting healthy lifestyle habits. This paper presents the protocol for the evaluation of the Power Up program, a study which aims to evaluate counselors' satisfaction with the Power Up services, trainings, and tools, their engagement in the program, as well as their self-efficacy and intention to promote physical activity, nutrition, and well-being through the camp environment. The secondary aim is to assess the program's effectiveness on physical activity, sedentary behaviors, and healthy eating among counselors and campers, along with the determinants of these behaviors.MethodsThis quasi-experimental study will evaluate the efficacy of implementing Power Up, a healthy lifestyle promotion program in summer camps. Power Up offers a range of services, trainings, and tools designed to assist camps in promoting healthy lifestyle habits, all developed based on the Social Cognitive Theory. Camps can choose from various services based on their needs, including personalized support, funding, challenge-based activities and contests. Training for camp counselors is provided with additional advanced workshops and webinars available. The program also includes over 150 tools to promote healthy lifestyle habits, such as physical activity, sedentary behaviors, and healthy eating. This study plans to enroll counselors aged 15 to 21 and campers aged 8 to 12 in two Canadian provinces from multiple summer camps over 3 years. Due to constraints that complicate the inclusion of a control group, an implementation score will be used to document the program's effects based on its degree of implementation in the camps. Descriptive statistics and MIXED linear models for repeated measures will be used to assess the effects of time, group (high vs. low implementation) and their interactions on behaviors and their determinants.ConclusionsThe results will provide evidence regarding the effectiveness of implementing Power Up to promote the adoption of healthy lifestyle habits among counselors and campers and its effect on the camp environment.